2017
DOI: 10.1002/ajh.24687
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 safety study of accelerated elotuzumab infusion, over less than 1 h, in combination with lenalidomide and dexamethasone, in patients with multiple myeloma

Abstract: Elotuzumab, an immunostimulatory SLAMF7-targeting monoclonal antibody, induces myeloma cell death with minimal effects on normal tissue. In a previous phase 3 study in patients with relapsed/ refractory multiple myeloma (RRMM), elotuzumab (10 mg/kg, 3-h infusion), combined with lenalidomide and dexamethasone, demonstrated durable efficacy and acceptable safety; 10% (33/321) of patients had infusion reactions (IRs; Grade 1/2: 29; Grade 3: 4). This phase 2 study (NCT02159365) investigated an accelerated infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Other early phase RRMM studies have reported deaths in early cycles. For example, Berenson and colleagues evaluated accelerated elotuzumab infusion in 70 patients with NDMM or RRMM, and reported two deaths (due to ischemic colitis and chronic obstructive lung disease) that occurred in patients who received only one cycle of treatment . Seven deaths were reported among 46 patients enrolled into a phase 1b study of panobinostat, lenalidomide, and dexamethasone .…”
Section: Discussionmentioning
confidence: 99%
“…Other early phase RRMM studies have reported deaths in early cycles. For example, Berenson and colleagues evaluated accelerated elotuzumab infusion in 70 patients with NDMM or RRMM, and reported two deaths (due to ischemic colitis and chronic obstructive lung disease) that occurred in patients who received only one cycle of treatment . Seven deaths were reported among 46 patients enrolled into a phase 1b study of panobinostat, lenalidomide, and dexamethasone .…”
Section: Discussionmentioning
confidence: 99%
“…Elotuzumab was infused weekly at 10 mg/kg for cycles 1 and 2 (28 days/cycle), and on days 1 and 15 during subsequent cycles. Infusion rate was increased, such that 5 mL/min (~1‐hour duration) was infused on cycle 1 day 15 and beyond . Dexamethasone 28 mg PO (3‐24 hours before) and 8 mg IV (immediately prior) preceded each infusion, with additional 40 mg given on weeks without elotuzumab starting with cycle 3.…”
Section: Methodsmentioning
confidence: 99%
“…Infusion rate was increased, such that 5 mL/min (~1-hour duration) was infused on cycle 1 day 15 and beyond. 4 Dexamethasone 28 mg PO (3-24 hours before) and 8 mg IV (immediately prior) preceded each infusion, with additional 40 mg given on weeks without elotuzumab starting with cycle 3. Standard pre-infusion therapy included acetaminophen 650 mg, ranitidine 50 mg IV or 150 mg PO, and diphenhydramine 25-50 mg, as well as acyclovir 400 mg BID as antiviral prophylaxis.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…11 75 The prescribing information states that the infusion rate may be increased to 5 mL/min after four treatment cycles, however a phase II safety study found no increase in AEs with a faster infusion of elotuzumab administered over 1 hour from the third dose onward. 88 ELOQUENT-2 and ELOQUENT-3 both gave elotuzumab at 10 mg/kg intravenous weekly for the first 8 weeks. However, in ELOQUENT-2, 10 mg/ kg was continued every 2 weeks for cycles 3 and beyond whereas in ELOQUENT-3, elotuzumab was given 20 mg/ kg intravenous every 4 weeks for cycle 3 and beyond.…”
Section: Administration Dosing and Monitoringmentioning
confidence: 99%